The Fagel Project - Jackson, Tim; McGowan, Moray; Van Berlo, Martine (Trinity College Dublin. Long Room Hub, 2008)
The East Pavilion of the Old Library houses the Fagel Collection - the books, pamphlets and maps amassed by a powerful Dutch family by the end of the 18th century. The Fagels having fallen on hard times as a result of the Napoleonic Wars, the entire library was to be auctioned by Christie's of London in March 1802. Through "Acumen" and "Timely Intervention" Trinity College bought the entire collection before it went to auction. Despite the immense wealth of this resource, it has only ever been examind sporadically and unsystematically. Indeed, large sections of the collection have never even been properly catalogued. The Department of Germanic Studies is preparing applications to Dutch, Belgian and Irish sources for funding for two postgraduate students or post-doctoral fellows to study the Fagel collection. The persons appointed would be expected either to study the collection itself, say, from the point of view of the history of the book or social history, or to carry out research projects based on its holdings, in areas such as literature, history of science, political history, cartography, or history of ideas.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Germanic studies; Fagel Collection; History; Cartography